From schooling access to learning outcomes, an unfinished agenda : an evaluation of World Bank support to primary education - Nielsen, H. Dean (World Bank e-Library., 2006)
The Education for All (EFA) movement, launched in 1990, has resulted in an extraordinary mobilization of World Bank and country resources in support of basic education over the past 15 years. World Bank EFA financing, mostly focused on primary education, has become increasingly progressive, targeting the most disadvantaged countries and often the disadvantaged within countries. In most parts of the world, Bank and country investments have led to significantly improved access to primary education through the construction of new schools and the reduction of other physical, financial, and social barriers. Nevertheless, tens of millions of children in the developing world--mostly girls, the poor, and other disadvantaged--remain out of school, hundreds of millions drop out before completing primary school, and of those who do complete, a large proportion fail to acquire desired levels of knowledge and skills, especially in the poorest countries of South Asia and Sub-Saharan Africa. Beyond achieving universal completion of primary education, a Millennium Development Goal (MDG), the remaining EFA challenge is to ensure that all children, particularly the disadvantaged, acquire the basic knowledge and skills that are crucial for poverty reduction. Over the years of Bank support for EFA and its world conferences in 1990 and 2000, the Bank's policy objectives for increased support to primary education have been simple and remarkably stable: universal primary school completion, equality of access for girls and other disadvantaged groups, and improved student learning outcomes. This Independent Evaluation Group (IEG) evaluation was mounted to assess the extent to which these objectives have been met in countries supported by the Bank. The main objectives of the evaluation were to assess World Bank assistance to countries in their efforts to improve their basic knowledge and skills base through the provision of quality primary education, and to provide lessons for countries in their development strategies and for the Bank in its support to those strategies.